Study of Alternative Shielding Material for Gamma Radiation using Monte Carlo Simulation - Urfa, Gusti Atika; Wianto, Totok; Manik, Tetti Novalina; Nasrulloh, Amar Vijai (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2026)
Lead is the most commonly used material for radiation shielding, even though it has toxic properties. This study aims to identify alternative, leadfree, and non-toxic materials for gamma radiation shielding using Monte Carlo simulations. Bismuth Oxide (Bi2O3), Barium Oxide (BaO), Tungsten Trioxide (WO3), Tungsten Dioxide (WO2), and Molybdenum Trioxide (MoO3) were selected as potential substitutes for lead. Pure lead (Pb) and Lead Oxide (PbO) were used for comparison. The simulation were performed using Particle Heavy Ion Tracking System (PHITS) software, with a gamma energy of 662 keV. The result of the simulation shows that the linear attenuation coefficient values for Pb and PbO were 0.902 mm-1 and 0.74 mm-1 respectively. Meanwhile, the simulation results of those simulated materials that are closest to Pb and PbO are Bi2O3 and WO2 with an attenuation coefficient of 0.71 mm-1. This simulation shows that for non-lead materials, BiO2 and WO2 have potential as alternative of non-lead radiation shielding.